Self‐Healing Elastic Electronics: Materials Design, Mechanisms, and Applications - Wan, Yi; Li, Xiang‐Chun; Yuan, Haotian; Liu, Daxiong; Lai, Wen‐Yong (Advanced functional materials, 2024)
Traditional electronic devices inevitably undergo degradation over time due to deformation, fatigue, or mechanical damage, ultimately resulting in device failure. To overcome this issue, researchers have pioneered the field of elastic electronics, incorporating higher mechanical tensile properties or strain resistance into electronic devices. Elastic materials, especially self‐healing elastomers (SHEs) are regarded as a crucial component in elastic electronics, offering the potential for restoring functionality and prolonging the lifespan of electronic devices. SHEs possess remarkable ability to tolerate significant deformation and utilize intrinsic dynamic chemical bonds to autonomously repair themselves from varying degrees of damage. The acquisition of intrinsic SHEs is key to the development of self‐healing elastic electronics and has attracted global attention. This review offers a comprehensive overview of the current advancements in self‐healing elastic electronics. First, the various self‐healing mechanisms present in elastomeric material systems are summarized. Second, the design strategies for constructing SHEs based on self‐healing mechanisms are reviewed in detail, with a particular emphasis on dynamic covalent and non‐covalent bonds. Subsequently, various optoelectronic applications of SHEs in elastic electronics are summarized. Finally, the challenges and prospects that lie ahead in order to foster further development in this rapidly growing field are outlined. In recent years, significant advancements have been made in self‐healing elastic electronics, including the design of self‐healing elastomers and corresponding elastic optoelectronic devices. Herein, a detailed and comprehensive overview of material design strategies including dynamic covalent/non‐covalent bonds is provided, and various optoelectronic applications including e‐skins, field effect transistors, energy storage devices, perovskite solar cells, and electroluminescent devices.